2016
DOI: 10.3389/fcimb.2016.00020
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Specific Signatures in the Transcriptional Response to Anaplasma phagocytophilum Infection of Ixodes scapularis and Ixodes ricinus Tick Cell Lines

Abstract: Anaplasma phagocytophilum are transmitted by Ixodes spp. ticks and have become one of the most common and relevant tick-borne pathogens due to their impact on human and animal health. Recent results have increased our understanding of the molecular interactions between Ixodes scapularis and A. phagocytophilum through the demonstration of tissue-specific molecular pathways that ensure pathogen infection, development and transmission by ticks. However, little is known about the Ixodes ricinus genes and proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 31 publications
2
46
0
Order By: Relevance
“…Infection of I. ricinus cells with flaviviruses leads to the differential expression of a large number of genes involved in a variety of cellular functions, including up-regulation of genes such as cytochrome c associated with cellular stress and apoptosis (Mansfield et al, 2017). However, the lack of detection of caspase genes, and the up-regulation of genes that inhibit apoptosis (including hsp70 ) suggest that flavivirus infection inhibits tick cell apoptosis in order to promote cell survival during infection as previously shown for A. phagocytophilum (Ayllón et al, 2015a; Alberdi et al, 2016). …”
Section: Biological Processes Involved In Tick-pathogen Interactionsmentioning
confidence: 90%
“…Infection of I. ricinus cells with flaviviruses leads to the differential expression of a large number of genes involved in a variety of cellular functions, including up-regulation of genes such as cytochrome c associated with cellular stress and apoptosis (Mansfield et al, 2017). However, the lack of detection of caspase genes, and the up-regulation of genes that inhibit apoptosis (including hsp70 ) suggest that flavivirus infection inhibits tick cell apoptosis in order to promote cell survival during infection as previously shown for A. phagocytophilum (Ayllón et al, 2015a; Alberdi et al, 2016). …”
Section: Biological Processes Involved In Tick-pathogen Interactionsmentioning
confidence: 90%
“…Gene knockdown by RNAi in ISE6 tick cells resulted in significantly lower A. phagocytophilum infection levels for both antigens when compared to control cells using the unrelated Rs86 dsRNA (Figure 6D ). These results suggested that although ISCW005600 and AAY66632 mRNA levels did not change in response to infection of ISE6 tick cells, which constitute a model for tick hemocytes involved in pathogen infection and immune response (Villar et al, 2015a ; Alberdi et al, 2016 ), they may play a role in A. phagocytophilum infection.…”
Section: Resultsmentioning
confidence: 90%
“…Recent results on the characterization of tick-host and tick-pathogen interactions highlighted the impact of I. scapularis genome sequence and assembly on these studies (Figure 1 ). Transcriptomics, proteomics and metabolomics studies showed the tissue-specific tick response to infection with Anaplasma phagocytophilum , the causative agent of HGA (Ayllón et al, 2015 ; Villar et al, 2015 ; Alberdi et al, 2016 ). Complementary proteomics analyses also revealed proteins associated with transmission of A. phagocytophilum and the encephalitis-causing Langat virus (Grabowski et al, 2016 ; Gulia-Nuss et al, 2016 ).…”
Section: The First Tick Genome Sequenced and Assembled: Results And Pmentioning
confidence: 99%